Analyzing gender equality in the US and Indonesian parliaments through liberal feminism theory - Holqi, Fikri Gali Fernando; Regita, Ardhia Saveria; Aprillia, Ana; A’yun, Izzah Qurotul (Universitas Islam Negeri Ar-Raniry, 2024)
Gender inequality is a persistent issue experienced by women worldwide, often intertwined with their limited participation in political spheres. This study examines the political involvement of women in the parliaments of Indonesia and the United States of America (USA) through the lens of liberal feminism theory. Employing qualitative decryption approaches with a comparative study design, data collected from both the Indonesian Parliament and the USA Parliament were understood, recorded, phrased, compared and analyzed within the framework of liberal feminism theory, focusing on the